A Utilisation of Improved Gabor Transform for Harmonic Signals Detection and Classification Analysis - M.H. Jopri; A.R. Abdullah; T. Sutikno; M. Manap; M.R. Yusoff (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper presents a utilization of improved Gabor transform for harmonic signals detection and classification analysis in power distribution system.  The Gabor transform is one of time frequency distribution technique with a capability of representing signals in jointly time-frequency domain and known as time frequency representation (TFR). The estimation of spectral information can be obtained from TFR in order to identify the characteristics of the signals. The detection and classification of harmonic signals for 100 unique signals with numerous characteristic of harmonics with support of rule-based classifier and threshold setting that been referred to IEEE standard 1159 2009. The accuracy of proposed method is determined by using MAPE and the outcome demonstrate that the method gives high accuracy of harmonic signals classification. Additionally, Gabor transform also gives 100 percent correct classification of harmonic signals. It is verified that the proposed method is accurate and cost efficient in detecting and classifying harmonic signals in distribution system.